PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEBIJAKAN DIVIDEN DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN - Liasti Wahyu Prihatin, 11.05.51.0105 (Students Journal of Economic and Management, 2015)
This research to analyze the effect of ownership structure to dividend policy and its impact to corporate value based on the value of the House of Representatives and PBV in the financial statements of manufacturing companies on the Stock Exchange for three years with the agency theory perspective and a bird in the hand theory. Appropriate agency theory and the theory of agency to resolve the conflict in the hands of birds are expecting a high dividend payout ratio to increase the value of the company. The results using regression prove that insider ownership has no effect on dividend policy, institutional ownership affect the dividend policy, dividend policy affects the corporateÂ value. This study supports the agency theory, signaling theory and a bird in the hand theory about how a company maximize dividend policy to increase the value of the company. Keywords: Insider Ownership, Institutional Ownership, Dividend Policy, Corporate Values